Proyecto de empresa para implementar una aplicación de monitoreo y desgaste en tiempo real de un vehículo - Carrillo Becerra, Sally Jarula (2023)
The present document analyzes the potential available market for a mobile application for smartphones that allows for real-time estimation of the wear and tear of the main and secondary parts of a vehicle. Furthermore, the technical and financial feasibility for the execution of this project is evaluated. The main differentiating factor is to provide the driver with timely and reliable information about their vehicle in a simple and comprehensive way, in addition to offering various functionalities that the competition does not consider. To achieve this, a survey was conducted among men and women between the ages of 25 and 54 in Lima Metropolitana, which identified that our business is primarily aimed at car owners or drivers who lack knowledge of automotive mechanics. We have identified an unmet need, as 86,5 % of the surveyed individuals who downloaded paid mobile applications expressed their willingness to pay for an app that provides real-time information on the wear and tear of the main parts of their vehicle. After analyzing the collected data through surveys, consumer behavior studies on social media, prototyping simulations, and a detailed financial analysis, it is concluded that the project is feasible and viable. Furthermore, it presents a high potential for scalability, and in the medium term, it could expand its scope of analysis to different types of vehicles, explore new lines of business, and broaden the offering to an international market.